STUDI PENERAPAN TRANSMEDIA STORYTELLING PADA IP KARAKTER DARTH VADER - Aditya Satyagraha; Gideon Kamang Frederick (Universitas Multimedia Nusantara, 2020)
Transmedia narrative has been evolved rapidly these days as well as its elements. One of the elements of transmedia who evolved is fictional characters. This paper will analyze the expansion of the fictional character from the transmedia world-building element to become a transmedial character through the hyperdiegesis and narrative braide principles. It will specifically discuss the character of Darth Vader from the Star Wars universe. The author will explore this character and describe its role in various media platform. This paper will also show how character development in transmedia storytelling is very dynamic, it can be an element in the transmedia story world, world-building can also be an element of the character itself, or even develop from the elements of world-building and create its world and complete the story world of the main universe.